A molecular dynamics study on the synergistic lubrication mechanisms of graphene/water-based lubricant systems. (March 2022) - Li, Chenjie; Tang, Weiwei; Tang, Xiu-Zhi; Yang, Linyan; Bai, Lichun
Abstract: Water-based lubricants with graphene have excellent lubrication behaviors, but the synergistic mechanism involving the activities of both water and graphene isblue still unclear. This work investigates such mechanism by considering the effect of different factors such as the number of water molecules, loading, surface roughness and sliding velocity via molecular dynamics simulation. It is found that the friction reduction by water-based lubricants is due to the enhanced isolation between friction pairs by the graphene presence and the improvement of water replenishment. The synergistic lubrication mechanism works as that the water molecules may protect the structural integrity of graphene by inducing its movement to release lateral stresses and the graphene can enhance the movement of water molecules and promote their rolling like bearings. Highlights: Water can protect the structural integrity of graphene by inducing its movement. Graphene can enhance the diffusions of water molecules and promote their rolling. Low friction is due to better water replenishments and pairs isolation by graphene. Water amount highly changes the friction force by affecting the contact interface. Friction fluctuation with water-based lubricants is insensitive to various loadings.